Insulin Dependent Diabetes Mellitus Control - Colmegna, Patricio Hernán (2013)
This work considers the problem of automatically controlling the glucose level in Insulin Dependent Diabetes Mellitus (IDDM) patients. The objective is to include several important and practical issues in the design: model uncertainty, time variations, nonlinearities, measurement noise, actuator delay and saturation, and real-time implementation. These are fundamental issues to be solved in a device implementing this control. A simulator of the well-known Sorensen 19-th state model has been built. It has been found that this compartmental model although nolinear, is almost Linear Time Invariant (LTI) in practice. To this end, a robust H-infinity controller is designed and tested against the simulator in order to check all the previous practical issues.